2001
DOI: 10.1164/ajrccm.164.10.2103140
|View full text |Cite
|
Sign up to set email alerts
|

Renal Effects of Nitric Oxide in Endotoxemia

Abstract: Nitric oxide (NO) is postulated to play a key role in the pathophysiology of renal failure in sepsis. Whether the renal effects of increased NO are beneficial or harmful remains unclear. In a porcine model of lipopolysaccharide (LPS)-induced shock, we evaluated the effect of LPS on glomerular filtration rate (GFR) and renal blood flow (RBF). We then administered the nonselective nitric oxide synthase (NOS) inhibitor N(G)-L-arginine methyl ester (L-NAME), and compared its effects on GFR and RBF with those of S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 14 publications
2
33
0
Order By: Relevance
“…S-methyl-isothiourea did not affect GFR and reduced sodium excretion. However, apart from increasing MAP, this selective inhibitor of iNOS offered little advantage to the kidneys as compared with saline resuscitation (64). In agreement, the degree of renal failure after LPS infusion was similar in iNOS knockout mice as compared with wild-type mice (43).…”
Section: Inhibition Of Nitric Oxide Synthasesupporting
confidence: 58%
See 1 more Smart Citation
“…S-methyl-isothiourea did not affect GFR and reduced sodium excretion. However, apart from increasing MAP, this selective inhibitor of iNOS offered little advantage to the kidneys as compared with saline resuscitation (64). In agreement, the degree of renal failure after LPS infusion was similar in iNOS knockout mice as compared with wild-type mice (43).…”
Section: Inhibition Of Nitric Oxide Synthasesupporting
confidence: 58%
“…Selective iNOS inhibition with S-methyl-isothiourea prevented hypotension through systemic vasoconstriction and maintained cardiac output and reduced the signs of renal dysfunction in rats challenged with LPS (63). In a hyperdynamic porcine model of sepsis, both L-NAME and S-methyl-isothiourea increased BP and caused comparable reductions of medullary and cortical blood flow (64). Only L-NAME was clearly detrimental to renal function by reducing GFR and increasing sodium excretion and renal oxygen extraction.…”
Section: Inhibition Of Nitric Oxide Synthasementioning
confidence: 93%
“…This renal failure may be the result of vasoconstriction in the kidney, resulting in a reduced glomerular filtration rate, as observed after experimental LPS (4,19,26,27). Sepsis and experimental endotoxemia upregulate NOS2 (21,23,25).…”
Section: L-guanidino-[mentioning
confidence: 97%
“…Continuous infusion of live bacteria, endotoxins as well as CLP are some of the methods used to induce sepsis in pigs. Porcine models of sepsis have been used extensively to investigate therapeutic agents focusing on improving renal, hepatic, intestinal and cardiovascular function (51)(52)(53). For instance, using a porcine model of LPS induced shock, Cohen et al observed that increasing levels of nitric oxide (NO) improves renal blood flow and glomerular filtration rate (51).…”
Section: Porcine Models Of Sepsismentioning
confidence: 99%
“…Porcine models of sepsis have been used extensively to investigate therapeutic agents focusing on improving renal, hepatic, intestinal and cardiovascular function (51)(52)(53). For instance, using a porcine model of LPS induced shock, Cohen et al observed that increasing levels of nitric oxide (NO) improves renal blood flow and glomerular filtration rate (51). In addition, the porcine model of fecal peritonitis has been previously used to investigate the impact of adding low dose arginine vasopressin (AVP) to norepinephrine infusion for improving organ function (52).…”
Section: Porcine Models Of Sepsismentioning
confidence: 99%